Rancangan Sistem Informasi Akademik Berbasis Website Menggunakan PHP dan MySQL - Ira Zulfa; Rizki Wanda (STMIK Budi Darma, 2023)
Society's demands on the quality of educational services are increasing from time to time. Along with the rapid development of science and technology, educational institutions at various levels and levels of education can no longer stand idly by to preserve the cultural capabilities and performance of a school, but must be persistent in innovating changes in various aspects so as not to be left behind by the people who live in in the era of globalization. Realizing this, schools as agents of change in society must always make changes in accordance with the dynamics of community development in the development of science and technology. Computer-based information technology is one medium that is quite effective in managing school academic information systems. One effort that can be used as a best practice flagship program for a school education institution is the creation of a school website which is seen as a golden bridge for achieving a bright future, moreover on this website there is a system that allows monitoring of student scores as evaluation material that can be monitored by parents/guardians in various places where processing can be done online. Besides that, various school information is also the main attraction for the community in viewing the image of the school. For this reason, it is appropriate for educational institutions to have websites as a means of communication between teachers, students and student guardians. In addition, the school's website can also be an information center for visitors and those who wish to continue their education at a higher level. MAN 2 Aceh Tengah is a madrasa education institution which was founded in 1992 in Central Aceh district. This MAN is classified as a school that has been around for a long time, so a website is needed to convey information to the public about school profiles, school facilities, school organizations, and others. The objectives of this research include designing and creating academic information system applications using the PHP and MySQL programming languages as databases, providing facilities and convenience for teachers and students in finding out school information and helping the public obtain complete and fast school information through this online website. as well as helping to promote MAN 2 Aceh Tengah. The results obtained in this study were the creation of a website-based academic information system at MAN 2 Aceh Tengah